Pengaruh Rasio Daun Meniran (Phyllanthus Niruri), Teh Hijau (Camellia Sinensis), dan Kayu Manis (Cinnamomum Burmanniic) terhadap Kandungan Antioksidan dalam Bentuk Herbal - Wahyu Maulidio, M.; Badruttamam, Ahmad; Puntri Pamungkas, Pinctada (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
Phyllanthus niruri (meniran), Camellia sinensis (green tea), and Cinnamomum burmannii (cinnamon) are known herbal ingredients with high antioxidant content. This study aimed to determine the effect of varying ratios of these three ingredients on the antioxidant content in the form of herbal tea. The method used was a Completely Randomized Design (CRD) with three different formulations: F1 (30% meniran, 20% green tea, 50% cinnamon), F2 (20% meniran, 30% green tea, 50% cinnamon), and F3 (10% meniran, 40% green tea, 50% cinnamon). Analysis was carried out using the DPPH method to test antioxidant activity, as well as organoleptic tests to evaluate taste, aroma, color, and texture. The results showed that the ratio of ingredients affected the antioxidant level, with formulation F3 showing the highest antioxidant activity at 94.34 ppm. However, ANOVA statistical analysis indicated that the differences between formulations were not significant. From an organoleptic perspective, formulation F1 received the highest scores, particularly in terms of aroma and color. The optimal combination was achieved through a formulation that balanced antioxidant effectiveness with consumer preference. Based on the research results, it can be concluded that variations in the ratio of meniran, green tea, and cinnamon influence the antioxidant content in herbal tea, although the differences were not statistically significant. Formulation F3, consisting of 10% meniran, 40% green tea, and 50% cinnamon, exhibited the highest antioxidant activity at 94.34 ppm, indicating that increasing the proportion of green tea may enhance antioxidant activity. On the other hand, based on the organoleptic test, formulation F1 (30% meniran, 20% green tea, 50% cinnamon) was the most preferred, especially in terms of aroma and color. Therefore, the ideal formulation is one that provides a balance between high antioxidant content and acceptable sensory characteristics, making it a potential functional herbal beverage product.